TECHNOLOGIES FOR FORMING VALEOLOGICAL CULTURE IN STUDENTS THROUGH FOLK GAMES (TAMADDUN NURI JURNALI, 2025)
This article provides detailed information about the system of forming valeological culture in female students through the use of folk games.